Ranula as the First Symptom of HIV Infection in Young Patients - X. Vanden Eynden; C. Bouland; D. Dequanter; M. Gerbaux; S. Kampouridis; E. Boutremans; I. Loeb (Case Reports in Pediatrics)
Introduction. Oral manifestations are often the earliest HIV signs. Salivary gland diseases are a common form of HIV expression. A ranula can occur in association with HIV. However, this manifestation is rarely considered as the disease sentinel sign. We present two cases of children consulting for a ranula, leading to the diagnosis of a previously unknown HIV infection. Case Reports. Two children, respectively, 5 and 13, were treated for a ranula by marsupialization. Relapse occurred in both cases, and thereafter, a ranula excision was performed. While the follow-up was uneventful, HIV infection was diagnosed during the patients’ care. The only sign or symptom observed was the ranula. A routine HIV testing of ranula patients would have allowed earlier care. Conclusion. Routine HIV testing of patients with a ranula is justified and may be recommended, especially for children. Ranula excision associated with the sublingual gland resection is suggested in order to avoid recurrence.